Effects of Communal Violence on Edikwu Communities in Apa Local Government Area (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This paper examined the effects of communal violence on Edikwu communities in Apa Local Government Area. The study was guided by one objective and research question. Descriptive survey research design was adopted for the study. The population of the study were selected adult population of male and female residents of Edikwu communities. The sample for the study were 200 participants randomly selected from the seventeen (17) communities that constitute Edikwu clan. Out of the 200 copies of questionnaire administered, 184 copies were returned representing 92% response rate. The findings of the study revealed that communal violence has led to increased displacement and migration of community members, disruption of social cohesion and community relationships, fear and mistrust among community members have increased, loss of lives and properties and has reduced access to health care services. The study concluded that the basic duty and function of the government is to provide security for the citizens of the country, it is rather unfortunate that the level of insecurity occasioned most recently in Edikwu communities in the Benue State in the most recent times is caused by herders/farmers conflict. The study recommended among others that there is need to implement policies reducing economic disparities, promote education and awareness as well as encourage interfaith dialogue and people-to-people initiatives. By addressing these factors, communities in Edikwu can reduce violence, promote social cohesion and sustainable peace.